2015
DOI: 10.1007/s00267-015-0585-y
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Surface Flow Constructed Wetlands (SFCW) for Nutrient Reduction in Drainage Discharge from Agricultural Fields in Denmark

Abstract: Constructed wetlands have been proposed as cost-effective and more targeted technologies in the reduction of nitrogen and phosphorous water pollution in drainage losses from agricultural fields in Denmark. Using two pig farms and one dairy farm situated in a pumped lowland catchment as case studies, this paper explores the feasibility of implementing surface flow constructed wetlands (SFCW) based on their cost effectiveness. Sensitivity analysis is conducted by varying the cost elements of the wetlands in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…CWs have been successfully used for treatment of many different types of wastewater [3,12,13], including agricultural drainage water. In general, CWs are more cost-effective for reducing non-point source pollution than other measures [14].…”
Section: Introductionmentioning
confidence: 99%
“…CWs have been successfully used for treatment of many different types of wastewater [3,12,13], including agricultural drainage water. In general, CWs are more cost-effective for reducing non-point source pollution than other measures [14].…”
Section: Introductionmentioning
confidence: 99%
“…The costs of SFCWs are related to land acquisition, construction, energy consumption (e.g., pumping in flat lands) and maintenance. Gachango et al [114] reported that these systems were able to retain P at relatively low cost (€55-1148 kg −1 P) in comparison to other measures. Moreover, the cost-efficiency improved when the SFCWs received higher P loads.…”
Section: Countrymentioning
confidence: 99%
“…Besides the benefit of CW in wastewater treatment, CWs could sustain wildlife habitats and biodiversity at local and global scales, as well as its potential usage in recreational and educational opportunities (Semeraro et al, 2015). On the cost aspect, it was shown that the cost effectiveness of the SFCW was higher in the drainage catchments with higher nutrient loads (Gachango et al, 2015). Natural wetlands degradation has been a serious global issue (Chen and Liu, 2015).…”
Section: Other Areas Of Considerationmentioning
confidence: 99%